(untitled) (Research, Society and Development, 2021)
This study aimed to describe the perception of women about the prevention of cervical cancer and the performance of the Pap smear. This is an integrative literature review, where the survey of the study was carried out between July and August 2021, through the MEDLINE, LILACS and BDENF databases. The Health Sciences Descriptors (DeCS) were used: Cervical Neoplasms, Pap smear and Women’s Health. After the inclusion and exclusion criteria and analysis of the studies, 16 studies were selected to compose the present study. The study shows that women attribute the Pap smear as fundamental for the prevention and early detection of diseases, however, they have insufficient knowledge about the Pap smear, a fact that is related to low education and low income, and that they have some negative feelings such as: pain, discomfort, embarrassment during the exam, fear of the result, anxiety, nervousness, shame, frustration and discomfort in taking the exam. The guidance of health professionals about the Pap smear for women who seek primary care services is essential. They should carry out health education actions on a continuous basis, emphasizing the importance of taking periodic Pap smears by women, providing greater adherence to the test, in addition to enabling humanized, continuous and quality care.